Capacious and programmable multi-liposomal carriers1. Issue 5 (7th February 2015) - Yaroslavov, Alexander A.; Sybachin, Andrey V.; Zaborova, Olga V.; Migulin, Vasiliy A.; Samoshin, Vyacheslav V.; Ballauff, Matthias; Kesselman, Ellina; Schmidt, Judith; Talmon, Yeshayahu; Menger, Fredric M.
<x xml:space="preserve">Abstract</x> pH-release from assembled polycationic brush liposomes.